A 2-bp deletion in the protein kinase domain region of the ERECTA-like receptor kinase gene in cucumber results in short internode phenotype. (February 2023) - Xu, Xuewen; Hu, Qiming; Wang, Jiaxi; Wang, Xueting; Lou, Lina; Xu, Jun; Yang, Xiaodong; Chen, Xuehao
Abstract: Cucumber varieties with shortend internodes require less space than regular vining varieties, thus have great significance for germplasm improvement. Here, we found a novel spontaneous cucumber mutant si107 that exhibited short intenodes (si), smaller leaves, fruits, and seeds. The decrease in longitudinal cell length led to the shortened internodes of si107. The genetic analysis revealed a single recessive gene si-2 that was responsible for the mutation. Through multiple lines of evidence, we demonstrated that CsSI is the possible candidate gene for si-2, which encodes an ERECTA leucine-rich repeat receptor-like kinase. The shortened internode in si107 is attributed to a 2-bp deletion in the protein kinase domain region of this gene. The expression of CsSI was higher in the internodes, petioles, and fruit peels of si107 than in the wild type (WT). The transcriptome analysis between the si107 mutant and WT indicated that differentially expressed genes were significantly enriched in the plant hormone signal transduction pathway, in which auxin signal genes comprised the largest group, and all were downregulated in si107. Phytohormone quantitation confirmed that endogenous auxin levels in the stems of si107 were decreased. Our results provide new insights into the molecular mechanisms underlying the internode length control in cucumber. Highlights: We identified a novel short internode mutant, si107, in cucumber. The shortened internodes in si107 is attributed to a 2-bp deletion in the ERECTA-like receptor kinase gene CsSI . CsSI regulates cucumber internode length through auxin signaling pathway.